(untitled) (Global Journal of Science Frontier Research, 2023)
This study investigated effect of wind velocity on CO2 fluxes at a tropical location Ile-Ife southwest Nigeria Halfhourly averaged flux data acquired by eddy covariance measurements conducted for a complete two-year period 2017-2018 over a grass-covered surface at Obafemi Awolowo University Ile-Ife Nigeria was analyzed The results showed that CO2fluxes increased rapidly from sunset to sunrise due to stable boundary layer and nighttime soil respiration Large transport of CO2 fluxes was very prominent in the early morning when winds were strong and large airmasses leaving the site Consequently CO2concentration dropped as convective activities kicked off enhancing photosynthesis CO2flux and concentration exhibited good linear relationships with relative humidity but strong inverse correlations with temperatures and radiations at the site The dominant wind flow in the area south westerly was largely responsible for transport and distribution of fluxes The study concluded that wind velocity has little or no significant influence on the transport and distribution of CO2 fluxes particularly at nighttime This may be attributed majorly to low frequency distribution of winds in the area